Macrophage variants in laboratory research: most are well done, but some are RAW - Herb, Marc; Schatz, Valentin; Hadrian, Karina; Hos, Deniz; Holoborodko, Bohdan; Jantsch, Jonathan; Brigo, Natascha (Frontiers in Cellular and Infection Microbiology, 2024)
Macrophages play a pivotal role in the innate immune response. While their most characteristic function is phagocytosis, it is important not to solely characterize macrophages by this activity. Their crucial roles in body development, homeostasis, repair, and immune responses against pathogens necessitate a broader understanding. Macrophages exhibit remarkable plasticity, allowing them to modify their functional characteristics in response to the tissue microenvironment (tissue type, presence of pathogens or inflammation, and specific signals from neighboring cells) swiftly. While there is no single defined “macrophage” entity, there is a diverse array of macrophage types because macrophage ontogeny involves the differentiation of progenitor cells into tissue-resident macrophages, as well as the recruitment and differentiation of circulating monocytes in response to tissue-specific cues. In addition, macrophages continuously sense and respond to environmental cues and tissue conditions, adjusting their functional and metabolic states accordingly. Consequently, it is of paramount importance to comprehend the heterogeneous origins and functions of macrophages employed in in vitro studies, as each available in vitro macrophage model is associated with specific sets of strengths and limitations. This review centers its attention on a comprehensive comparison between immortalized mouse macrophage cell lines and primary mouse macrophages. It provides a detailed analysis of the strengths and weaknesses inherent in these in vitro models. Finally, it explores the subtle distinctions between diverse macrophage cell lines, offering insights into numerous factors beyond the model type that can profoundly influence macrophage function.